Prognostic Value of Inflammatory Mediators in 1-Year Outcome of Acute Ischemic Stroke with Middle Cerebral Artery Stenosis - Xiping Gong; Xinying Zou; Liping Liu; Yuehua Pu; Yilong Wang; Yuesong Pan; Yannie O. Y. Soo; Thomas W. H. Leung; Xingquan Zhao; Yongjun Wang; Ka Sing Wong (Mediators of Inflammation)
Background and Purpose. Inflammation exists in inception, progression, and reperfusion of acute ischemic stroke. Insightful understanding of correlation in inflammatory mediators and stroke severity with intracranial artery stenosis may improve rational stroke therapy. Methods. We prospectively recruited 977 patients with acute noncardioembolic ischemic stroke with MCA stenosis by MRA as none to mild (<50%), moderate (50–69%), severe (70–99%), or occlusive (100%). The peripheral levels of WBC, homocysteine (HCY), and high sensitivity C-reactive protein (hs-CRP) were recorded. All patients were assessed of 1-year outcome by mRS as favorable (0–2) or poor (3–6). Results. The levels of WBC, HCY, and hs-CRP had no significant differences in patients with categorized MCA stenosis (all . Higher levels of WBC, HCY, and hs-CRP were found in patients with 1-year poor outcome (all , but only hs-CRP is an independent predictor (OR 1.06, 95% CI 1.027–1.093, . The combination of any two of increased hs-CRP (>3 mg/L), WBC (>6.91 × 109/L), and HCY (>15 μmol/L) had higher power in predicting 1-year poor outcome than the single elevated mediator. Conclusions. Elevated hs-CRP independently predicts 1-year poor outcome in acute stroke. The combination of increased hs-CRP, WBC, or HCY had a stronger predictive value in poor outcome than individual elevated mediator.